2019
DOI: 10.15294/harmonia.v19i2.23623
|View full text |Cite
|
Sign up to set email alerts
|

Weak of Effects of Music Education in The Establishment of Characters

Abstract: This study discusses the absence of significant influence from music education in shaping an individual’s character. Character education itself is an education that discusses the mental and moral qualities that are unique to an individual. Ki Hajar Dewantara views music education as having the power to help Indonesian people realize a better inner and outer life, and the nature of the art of music itself is actually order and beauty. The purpose of this study is to reveal the weak influence of music education … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
(14 reference statements)
0
3
0
1
Order By: Relevance
“…Using MUE can cultivate the individual's subjective initiative university students' PT. Among them, Wicaksono said that long-term MUE can make the psychology of university students healthier and help cultivate the subjective initiative of university students in PT [ 6 ]. Payne et al concluded that MUE can make the mental state of university students healthier by surveying the mental health of MUE.…”
Section: Introductionmentioning
confidence: 99%
“…Using MUE can cultivate the individual's subjective initiative university students' PT. Among them, Wicaksono said that long-term MUE can make the psychology of university students healthier and help cultivate the subjective initiative of university students in PT [ 6 ]. Payne et al concluded that MUE can make the mental state of university students healthier by surveying the mental health of MUE.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the similarity of these elements, of course, there are variations in the cultural structure of each existing community. Therefore, in the context of art, at its development stage, it is often used as a distinctive and traditional identity that is owned by the community itself and grows in an artistic environment that is different from one another (Wicaksono, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The attachment of digitalization to every aspect of human life today is one of the factors of the moral and ethical crisis in the current generation. It will even result in the elimination of existing traditional arts if conservation efforts are not made through interesting platforms that keep up with the times (Harjono & Rachman, 2018;Rachman & Pribadi, 2019;, 2019Simeon, 2015;Simeon et al, 2017;Zahrotul & Rachman, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…2020) Filosofi Ki hajar dewantara menyebutkan bahwa tugas seorang pendidik adalah menuntun anak untuk tumbuh dan berkembang sesuai kodratnya dalam mencapai kebahagiaan dan keselamatan. Sehingga dapat dikatan pendidik mebimbing dan menuntun anak sesuai dengan potensi, minat, dan bakat serta kemampuan yang dimiliki untuk mencapai keberhaslan dan kebahagiaan (Fahmi, 2020;Ferary, 2023;Marini, 2023;Suciptaningsih, 2020;Supeni, 2019;Tarto, 2019;Wicaksono, 2019).…”
Section: Pendahuluanunclassified